(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In this paper, the subject of the study is the history of the emergence and origin of the customs of mutual assistance among the Kyrgyz people. The study of the origin of the traditions of mutual assistance of the Kyrgyz people, their historical formation and social significance. The article provides a detailed overview and analysis of how customs such as ashar, kudagy zhana jeenderdin meeneti, sadaka, Kurman ait and orozo ait arose and developed, moral values that are described in the epic Manas. From a scientific point of view, an analysis of the origin and development of the customs of mutual assistance of the Kyrgyz people is given, and how these customs functioned in the conditions of the nomadic lifestyle of the Kyrgyz, maintaining the stability and cohesion of the community. The article uses a historical method that helps to identify not only the events of the past, but also social mechanisms, cultural values and worldviews that have been formed over the centuries. The scientific value of the results obtained is the expansion of knowledge about the historical development of these customs, their importance for community cohesion and adaptation to harsh living conditions. Historical and graphic recommendations are useful for understanding complex historical data and phenomena, improves understanding and perception of the origin of these traditions. The description of the article allows us to assess the traditions of the Kyrgyz people, which, despite the influence of globalization and urbanization, continue to play an important role in the life of society.